ChemInform Abstract: Growth of Highly Epitaxial YBa2Cu3O7‐δ Films from a Simple Propionate‐Based Solution. Issue 2 (23rd December 2015) - Zhao, Yue; Torres, Pol; Tang, Xiao; Norby, Poul; Grivel, Jean‐Claude
Abstract: Superconducting YBa2 Cu3 O7‐ δ (YBCO) films are deposited on LaAlO3 single crystals from fluorine‐free 1.5‐1.7 M precursor solutions containing a stoichiometric mixture of Y, Ba, and Cu acetates in propionic acid (80 °C, 1 h).